BMP‐ and TGFβ‐signaling regulate the formation of Müller glia‐derived progenitor cells in the avian retina. Issue 10 (13th July 2017) - Todd, Levi; Palazzo, Isabella; Squires, Natalie; Mendonca, Ninoshka; Fischer, Andy J.
Abstract: Müller glia‐derived progenitor cells (MGPCs) have the capability to regenerate neurons in the retinas of different vertebrate orders. The formation of MGPCs is regulated by a network of cell‐signaling pathways. The purpose of this study was to investigate how BMP/Smad1/5/8‐ and TGFβ/Smad2/3‐signaling are coordinated to influence the formation of MGPCs in the chick model system. We find that pSmad1/5/8 is selectively up‐regulated in the nuclei of Müller glia following treatment with BMP4, FGF2, or NMDA‐induced damage, and this up‐regulation is blocked by a dorsomorphin analogue DMH1. By comparison, Smad2/3 is found in the nuclei of Müller glia in untreated retinas, and becomes localized to the cytoplasm following NMDA‐ or FGF2‐treatment. These findings suggest a decrease in TGFβ‐ and increase in BMP‐signaling when MGPCs are known to form. In both NMDA‐damaged and FGF2‐treated retinas, inhibition of BMP‐signaling suppressed the proliferation of MGPCs, whereas inhibition of TGFβ‐signaling stimulated the proliferation of MGPCs. Consistent with these findings, TGFβ2 suppressed the formation of MGPCs in NMDA‐damaged retinas. Our findings indicate that BMP/TGFβ/Smad‐signaling is recruited into the network of signaling pathways that controls the formation of proliferating MGPCs. We conclude that signaling through BMP4/Smad1/5/8 promotes the formation of MGPCs, whereas signaling through TGFβ/Smad2/3 suppresses the formation of MGPCs. Main Points: Using the chick model system to study the retina in vivo, we find that cell signaling through BMP4/Smad1/5/8 stimulates the formation of proliferating Müller glia derived progenitor cells, whereas TGFβ2/Smad2/3 suppresses this process.